Effect of Regulated Irrigation Deficit Treatments on fruit physical and chemical quality of two date palm fruit cultivars ’Sayer’ and ’Hallawi’ - Ali Abdulrahman Fadhil/Abdul-Kareem M. Abd/AbdulminamH.Ali ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The current study aimed to investigate the effects of irrigation deficit treatments on physical and chemical characteristics of the fruits two date palm cultivars ’Sayer’ and ’Hallawi’ for the at the Khalal ,Rutab and Tamar stages. The date palm trees of two cultivars were selected in the same age and subjected to same agricultural services as much as possible. Four deficit irrigation treatment were applied on date palm trees under study as follow (150 liter/week, 150 liter/10 days, 150 liter/ 20days and 150 liter/30days). The results showed a significant superiority of cultivar ’Hallawi’ on cultivar ’Sayer’ in fruit weight (7.689 g), fruit flesh weight (6.364 g) and fruit size (7.51 mm3) at the Khalal stage. Results also revealed the increases in the ratio of soluble solids (56.06%) and the percentage of total sugars (53.11%). Results conclude that the interaction between cultivar and irrigation treatments had a significant effect on the physical and chemical traits of the fruits yield DOI /10.54633/2333-021-042-005